Analisis Pengaruh Variasi Kecepatan Putar (RPM) Terhadap Kinerja Mesin Pencacah Rumput - Tri Tam Tomo; Budi Harjanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to analyze the performance of a grass chopping machine with a controlled cutting size system in terms of chopping capacity and quality of the cutting results. The background of this research is driven by the need for efficient, uniform, and easily digestible forage for livestock. The method used is an experimental approach with variations in rotational speed (RPM) and feeding mechanism as independent variables, while chopping capacity and cutting length are treated as dependent variables. Data were collected through direct testing of the designed machine by measuring processing time, material weight, and the length of the chopped output. The results indicate that increasing rotational speed significantly improves chopping capacity; however, it also tends to produce shorter and less uniform cutting results. In addition, a stable feeding mechanism contributes to more consistent cutting quality. Therefore, an optimal combination of operational parameters is essential to achieve the best machine performance. This research is expected to serve as a reference for the development of more efficient and practical grass chopping machines for livestock feeding systems.